$\mathcal{I}_{2}$-Asymptotically Lacunary Statistical Equivalence of Weight $g$ of Double Sequences of Sets - Kişi, Ömer (Sarajevo Journal of Mathematics, 2022)
In this paper, our aim is to introduce new notions, namely, Wijsman asymptotically $\mathcal{I}_{2}$-statistical equivalence of weight $g$, Wijsman strongly asymptotically $\mathcal{I}_{2}$-lacunary equivalence of weight $g$ and Wijsman asymptotically $\mathcal{I}_{2}$-lacunary statistical equivalence of weight $g$ of double set sequences. We mainly investigate their relationship and also make some observations about these classes.